Iatrogenic Opioid Withdrawal in Critically Ill Patients: A Review of Assessment Tools and Management. (December 2017) - Chiu, Ada W.; Contreras, Sofia; Mehta, Sangeeta; Korman, Jennifer; Perreault, Marc M.; Williamson, David R.; Burry, Lisa D.
Objective: To (1) provide an overview of the epidemiology, clinical presentation, and risk factors of iatrogenic opioid withdrawal in critically ill patients and (2) conduct a literature review of assessment and management of iatrogenic opioid withdrawal in critically ill patients.Data Sources: We searched MEDLINE (1946–June 2017), EMBASE (1974–June 2017), and CINAHL (1982–June 2017) with the terms opioid withdrawal, opioid, opiate, critical care, critically ill, assessment tool, scale, taper, weaning, and management. Reference list of identified literature was searched for additional references as well aswww.clinicaltrials.gov .Study Selection and Data Extraction: We restricted articles to those in English and dealing with humans.Data Synthesis: We identified 2 validated pediatric critically ill opioid withdrawal assessment tools: (1) Withdrawal Assessment Tool–Version 1 (WAT-1) and (2) Sophia Observation Withdrawal Symptoms Scale (SOS). Neither tool differentiated between opioid and benzodiazepine withdrawal. WAT-1 was evaluated in critically ill adults but not found to be valid. No other adult tool was identified. For management, we identified 5 randomized controlled trials, 2 prospective studies, and 2 systematic reviews. Most studies were small and only 2 studies utilized a validated assessment tool. Enteral methadone, α-2 agonists, and protocolized weaning were studied.Conclusion: We identified 2 validated assessment tools for pediatric intensive care unit patients; no valid tool for adults. Management strategies tested in small trials included methadone, α-2 agonists, and protocolized sedation/weaning. We challenge researchers to create validated tools assessing specifically for opioid withdrawal in critically ill children and adults to direct management.